Cycloadditions with a Stable Charge‐Separated Cyclobutadiene‐Type Amido‐Substituted Silicon Ring Compound. Issue 40 (31st August 2021) - Keuter, Jan; Hepp, Alexander; Daniliuc, Constantin G.; Feldt, Milica; Lips, Felicitas
Abstract: Reductive debromination of {N(SiMe3 )2 }SiBr3 with Rieke magnesium results in the formation of the five‐vertex silicon cluster with one bromine substituent Si5 {N(SiMe3 )2 }5 Br, 1, and the cyclobutadiene analogue 2 in a 1:1 ratio. The latter features a planar four‐membered silicon ring with a charge‐separated electronic situation. Two silicon atoms in 2 are trigonal planar and the other two trigonal pyramidal. In cycloadditions with ethylene, diethylacetylene, 1, 5‐cyclooctadiene, and 2, 3‐dimethyl‐1, 3‐butadiene cyclic unsaturated ring compounds (3 –6 ) were formed at room temperature in quantitative reactions. Two of the products (3 and 6 ) show photochemical isomerization with LED light (λ=405 nm) to afford saturated ring compounds 4 e and 6′ . Abstract : The reductive debromination of {N(SiMe3 )2 }SiBr3 with activated magnesium yields a cyclobutadiene‐type silicon ring compound 2 with a charge‐separated electronic situation, which undergoes cycloadditions with alkenes and alkynes to yield unsaturated bicyclic and tricyclic silicon ring compounds with Si=Si and/or C=C double bonds (3 –6 ).